Polyphenols as active ingredients for cosmetic products. (16th March 2015) - Zillich, O. V.; Schweiggert‐Weisz, U.; Eisner, P.; Kerscher, M.
Synopsis Polyphenols are secondary plant metabolites with antioxidant, anti‐inflammatory and anti‐microbial activity. They are ubiquitously distributed in the plant kingdom; high amounts contain, for example, green tea and grape seeds. Polyphenolic extracts are attractive ingredients for cosmetics and pharmacy due to their beneficial biological properties. This review summarizes the effects of polyphenols in the context of anti‐ageing activity. We have explored in vitro studies, which investigate antioxidant activity, inhibition of dermal proteases and photoprotective activity, mostly studied using dermal fibroblasts or epidermal keratinocytes cell lines. Possible negative effects of polyphenols were also discussed. Further, some physicochemical aspects, namely the possible interactions with emulsifiers and the influence of the cosmetic formulation on the skin delivery, were reported. Finally, few clinical studies, which cover the anti‐ageing action of polyphenols on the skin after topical application, were reviewed.